If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 9x + 1 Reorder the terms: -2 + 4x = 9x + 1 Reorder the terms: -2 + 4x = 1 + 9x Solving -2 + 4x = 1 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -2 + 4x + -9x = 1 + 9x + -9x Combine like terms: 4x + -9x = -5x -2 + -5x = 1 + 9x + -9x Combine like terms: 9x + -9x = 0 -2 + -5x = 1 + 0 -2 + -5x = 1 Add '2' to each side of the equation. -2 + 2 + -5x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 1 + 2 -5x = 1 + 2 Combine like terms: 1 + 2 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6
| -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= | | -6(-3a-4)= | | -17r=17 | | -5+11x=11x-5 | | -8/3b=5/1 | | 25-x/8=12.5 | | 1/3x+7=14 | | 6y/7-3/8y | | m+5m-5=7 | | 2x+7x-4=95 | | 900/16 | | 6(2x-4)=4 | | (1/3)(x-3)=4-(2x+3) | | 5(1-4x)+x= | | 4+2/5x=4/15x | | 0.45x+0.05(4-x)=0.10(34) | | (128x^8y^12)^(1/6) | | 2.5x+7.8=12.2 | | 5s+36=3s+6 | | 6x+3y+5x=0 | | -16-6x=-4x+12 | | 7x-9=24+7x | | N+2=-14n | | 8y+4(1+y)=3(y-3)+10y | | 2.5x=4.4 | | -3(1+7a)+a= | | -5/6+1/12 | | 0.46x+0.05(4-x)=0.10(34) | | y=--5+2 |